Resiprositas Indonesia dan Australia dalam Kerja Sama Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) Periode Tahun 2020-2021 - Fika Aulia Anfasa (Ecoplan, 2023)
Indonesia and Australia both ratified the comprehensive economic partnership, agreement Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA), to improve Indonesia's export performance to Australia. However, after the IA-CEPA cooperation started, Indonesia's trade balance became increasingly deficit. It raised the assumption that Indonesia's benefits in this cooperation differed from those obtained by Australia. Therefore, this study examines the interchange between the two countries under IA-CEPA cooperation in 2020-2021. The research method used is qualitative, with descriptive analysis and triangulation to test the validity of the data. The results of this study indicate that even though Indonesia's trade balance with Australia during the IA-CEPA cooperation period experienced a deficit, the two countries both received mutual benefits according to their individual needs, where Australia benefited through increasing its exports to Indonesia and Indonesia. Helped through various economic assistance programs provided by Australia.